TAKING ON TOO MUCH AT ONCE? - DAVIDSON, JEFFX (Public Management (00333611), 2016)
The article discusses the downside of multitasking given the large amount of information available and communication overload that impacts the ability to complete a task. Topics include the increased in processing speed with lack of comprehension, the problems associated with multitasking, and the potential hazards of multitasking which could lead to diminished productivity including gaps in short-term memory, loss of concentration, and communication problems.